2018
DOI: 10.1177/0004867418762057
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on treatment of perinatal depression with antidepressants: An international review

Abstract: Objective:Several countries have developed Clinical Practice Guidelines regarding treatment of perinatal depressive symptoms and perinatal use of antidepressant. We aimed to compare guidelines to guide clinicians in best clinical practice.Methods:An extensive search in guideline databases, MEDLINE and PsycINFO was performed. When no guidelines were (publicly) available online, we contacted psychiatric-, obstetric-, perinatal- and mood disorder societies of all first world countries and the five largest second … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
94
0
12

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(111 citation statements)
references
References 44 publications
(46 reference statements)
5
94
0
12
Order By: Relevance
“…We observed that the teratogenic medicines with the highest prevalence of use in the first trimester were psychotropics and antibiotics . In some patients with conditions often treated with psychotropics, for example depression, non‐pharmacological therapies are beneficial; however, this approach is not always effective . Antiepileptics, which accounted for most of the psychotropic use in our study, may cause fetal malformations and neurodevelopmental disorders in children exposed in utero .…”
Section: Discussionmentioning
confidence: 64%
“…We observed that the teratogenic medicines with the highest prevalence of use in the first trimester were psychotropics and antibiotics . In some patients with conditions often treated with psychotropics, for example depression, non‐pharmacological therapies are beneficial; however, this approach is not always effective . Antiepileptics, which accounted for most of the psychotropic use in our study, may cause fetal malformations and neurodevelopmental disorders in children exposed in utero .…”
Section: Discussionmentioning
confidence: 64%
“…Any affected pregnant woman, and their health care professional, therefore faces a complex decision regarding initiation, continuation or discontinuation of SSRIs. Internationally, guidelines agree on a limited set of recommendations, such as the use of psychotherapy as preferred treatment in mild to moderate depression (Molenaar et al 2018b). But on key aspects of the dilemma, guidelines are unclear (conflicting recommendations or no reference to the topic), i.e., on the firstchoice drug and on when and how to switch to another antidepressant, leading to considerable variation in current practice (Molenaar et al 2018a;Ververs et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A recent international analysis of clinical practice guidelines for treatment of perinatal depression found that among 16 international guidelines, most guidelines, including the American Psychiatric Association (US), Centre of Perinatal Excellence (Australia), and National Institute for Health and Care Excellence (UK), agree that psychotherapy, and in particular CBT, should be used as initial treatment in mild to moderate depression during pregnancy 157. Most guidelines indicate that an approach focused on antidepressant drug treatment should be used in severe depression in pregnancy 157. Only the American College of Obstetricians and Gynecologists determined that antidepressants should be used as initial treatment instead of psychotherapy during pregnancy, independent of severity of depression.…”
Section: Guidelinesmentioning
confidence: 99%
“…Only the American College of Obstetricians and Gynecologists determined that antidepressants should be used as initial treatment instead of psychotherapy during pregnancy, independent of severity of depression. In the postpartum period, most guidelines agree that psychotherapy should be the initial treatment for mild to moderate depression, with consideration of antidepressants as initial treatment for severe depression, and most encourage continued breast feeding, independent of the type of antidepressant drug 157. Of note, these guidelines favor a personalized approach to treatment, based on detailed history that allows for identification of clinical characteristics to guide individualized treatment.…”
Section: Guidelinesmentioning
confidence: 99%